STRATEGI PEMERINTAH DESA TERKAIT REALISASI DESA WISATA DI DESA NEGLAWANGI KECAMATAN KERTASARI KABUPATEN BANDUNG - Rendy Adiwilaga; Ujud Rusdia (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
Neglawangi Village is an interesting locus to study, considering that 70% of its territory is a tea plantation managed directly by PTPN, as well as a protected forest managed by Perhutani. The remaining 30% of the area is used as a settlement for local residents. In addition, Neglawangi Village actually does not have strategic assets like village markets and so on, but interestingly, Neglawangi Village has a master plan in realizing a tourist village with a target of 2021 (postponed to 2025 due to the covid-19 pandemic constraints) by utilizing points - tourist points that can be exploited into commodities of local wisdom that can potentially attract tourists. This research was studied using the Bintoro Tjokroamidjojo strategy theory, with problem dissection through descriptive qualitative methods combined with SWOT analysis as a social mapping effort taken through long observations for 2 months, combined with tourism destination development indicators that refer to the Destination Development Guidelines. Rural Tourism, formulated by the Ministry of Tourism. The indicator points are identity, zoning, tourist attraction, activities, accessibility, amenities, community / population, investment, tourism businesses, institutions, and finally marketing. The results showed that Neglawangi Village has great potential such as various natural tourism points, historical tourism, and cultural tourism. However, plans for developing tourist sites collide with other parties such as the BKSDA and other nature lovers organizations because some tourist destinations are nature reserves. Operationalization is still hampered by changes in the reins of power in the provincial and district domains which have implications for external development budget allocations. Because if you rely on the Village Fund, the Tourism Village is difficult to materialize because it requires large logistics.